Genomic Breed Composition of Selection Signatures in Brangus Beef Cattle - Paim, Tiago do Prado; Hay, El Hamidi A.; Wilson, Carrie; Thomas, Milt G.; Kuehn, Larry A.; Paiva, Samuel R.; McManus, Concepta; Blackburn, Harvey (Frontiers in Genetics, 2020)
Cattle breeding routinely uses crossbreeding between subspecies (B. taurus taurus and B. taurus indicus) to form composite breeds such as Brangus. These composite breeds provide an opportunity to identify recent selection signatures formed in the new population and evaluate the genomic composition of these regions of the genome. Using high density genotyping, we first identified runs of homozygosity (ROH) and calculated genomic inbreeding. Then, we evaluated the genomic composition of the regions identified as selected (selective sweeps) using a chromosome painting approach. The genomic inbreeding increased at approximately 1% per generation after composite breed formation, showing the need of inbreeding control even in composite breeds. Three selected regions in Brangus were also identified as Angus selection signatures. Two regions (Chromosomes 14 and 21) were identified as signatures of selection in Brangus and both founder breeds. Five of the 10 homozygous regions in Brangus were predominantly Angus in origin (probability > 80%) and the other five regions had a mixed origin, but always with Brahman contributing less than 50%. Therefore, genetic events such as drift, selection and complementarity are likely shaping the genetic composition of founder breeds in specific genomic regions. Such findings highlight a variety of opportunities to better control the selection process and explore heterosis and complementarity at the genomic level in composite breeds.